Effect of organic silicon on the yield of passion fruit (Passiflora edulis), cultivated in Somate- Sullana - Peña Castillo, Ricardo Antonio (2019)
The investigation was carried out in a passion fruit plantation (Passiflora edulis) installed in the village of Somate Alto - Sullana; previously the soil analysis was performed. The objective of this study was to evaluate the effect of organic silicon on yield, quality and economic profitability, for which the Random Complete Blocks design was used. The experimental unit consisted of 12 plants, evaluating the 4 plants for the yield parameters and 2 for the quality parameters. The treatments were: T0 (control without silicon), T1 T2, T3 and T4 with 25, 50, 75 and 100 kg.ha-1 of organic silicon respectively. The evaluations were made until the fifth harvest of fruits with commercial maturity (first three months of harvest); The conclusions were: - The best treatment for yield was T0 (control) with 10589,87 Kg.ha-1 of fruit, however, T0 behaved statistically equal to the rest of treatments in the juice pH parameter and only exceeded to T2 (50 kg.ha-1 of silicon) in the volume of juice. - Regarding total soluble solids, T0 was statistically exceeded by the rest of treatments. - There were no significant differences between treatments T3 (75 kg.ha-1 of silicon), T4 (100 kg.ha-1 of silicon) and T0 (control) in fruit weight and juice volume. - The Control Treatment (T0), had the highest economic profitability with a benefit / cost ratio of 1,41.